The Role Of Pictures And Videos In The Learning Independence Of Elementary School Students - Juarni Siregar; Wa Ode Riniati; Firman Aziz; Devin Mahendika; Dahlan Abdullah (Departement of Mathematics Education, 2023)
This study demonstrates that the advancement of technology has a significant impact on the use of images and videos as learning material, enhancing accessibility, interactivity, visual quality, and learning efficacy/efficiency. This study's objective is to examine the role of image and video elements in learning media that promote student independence. The research will give information on the effect of the utilization of images and videos on the independent learning of primary school children. Give information on how the usage of visuals and videos can boost the connection between information and elementary school students' comprehension. Utilizing the process of a literature review, the research gives recommendations on the use of images and videos to help students comprehend the subject matter, boost learning motivation, facilitate information storage, and foster creativity. Students' learning independence can be maximized by implementing techniques such as scaffolding, problem-based learning, inquiry-based learning, project-based learning, flipped classroom, and game-based learning. More research is required to analyze the efficacy of the use of images and videos, students' preferences for learning media, the adoption of optimization strategies, and the significance of images and videos in promoting primary school students' learning independence.